(untitled) (TAJDID: Jurnal Ilmu Ushuluddin, 2022)
Deradicalization is interpreted as a step to return the paradigm of exclusivity towards an understanding of inclusiveness. However, in practice, deradicalization is only carried out at a normative level, namely changing the paradigm. In fact, if explored more deeply, deradicalization should touch the background of the involvement of terrorist groups. This study not only discusses the steps of deradicalism as a form of guidance and protection for former terrorists so that they can be rehabilitated but also provides an ideal deradicalization solution by exploring the motives of the aspects that influence it. This research was conducted at the Lingkar Perdamaian Foundation, one of the institutions that participated in the deradicalization program, thus presenting two questions; what is the deradicalization strategy at the Lingkar Perdamaian Foundation, and how the implications of this deradicalization are carried out. To obtain these answers, this study used descriptive qualitative methods by conducting interviews, observations, and documentation as data collection tools. This research shows the strategy carried out by the Lingkar Perdamaian Foundation into three things; first, through ideological development, assistance to families of ex-terrorist convicts, and economic recovery. All of these strategies are measured based on needs, as Abraham Maslow’s theory regarding the hierarchy of needs, the availability of the above needs is intended so that they do not repeat the terror in their past, this will change the perspective of extremist ideology to a tolerant ideology. The implications of deradicalization at the Lingkar Peace Foundation are marked by the opening of an inclusive understanding that accepts all forms of differences in religious views and believes in the Unitary State of the Republic of Indonesia as the legitimate homeland. Deradikalisasi dimaknai sebagai langkah untuk mengembalikan kembali paradigma ekslusifitas menuju pemahaman inklusifitas. Akan tetapi dalam praktiknya, deradikalisasi hanya dilakukan pada level yang normatif, yakni sekedar merubah paradigma. Padahal jika ditelusuri lebih dalam seharusnya deradikalisasi menyentuh latarbelakang keterlibatan kelompok teroris. Kajian ini bukan hanya membahas mengenai langkah deradikalisme sebagai bentuk pembinaan dan perlindungan bagi mantan teroris agar dapat direhabilitasi, tetapi juga memberi solusi deradikalisasi ideal dengan menelusuri motif aspek yang mempengaruhinya. Penelitian ini dilakukan di Yayasan Lingkar Perdamaian, salah satu lembaga yang turut melakukan program deradikalisasi, sehingga menghadirkan dua pertanyaan; bagaimana strategi deradikalisasi di Yayasan Lingkar Perdamaian (YLP), dan bagaimana implikasi deradikalisasi tersebut dilakukan. Untuk memperoleh jawaban tersebut penelitian ini menggunakan metode kualitatif deskriptif dengan melakukan wawancara, observasi dan dokumentasi sebagai alat pengumpulan data. Penelitian ini menunjukan strategi yang dilakukan Yayasan Lingkar Perdamaian kedalam tiga hal; pertama, melalui pembinaan ideologi, pendampingan keluarga mantan napiter dan pemulihan ekonomi. Semua strategi ini diukur berdasarkan kebutuhan, sebagaimana teori Abraham Maslow mengenai hierarchy of need, ketersediaan kebutuhan di atas dimaksudkan agar mereka tidak kembali mengulangi teror di masa lalunya, hal ini akan mengubah cara pandang ideologi ekstrimis menuju ideologi toleran. Adapun implikasi dari deradikalisasi di Yayasan Lingkar Perdamaian di tandai dengan terbukanya pemahaman inklusif yang menerima segala bentuk perbedaan dalam pandangan agama serta meyakini NKRI sebagai tanah air yang sah.